A Process Perspective on Regulation: A Grounded Theory Study into Regulatory Practice in Newly Liberalized Network-Based Markets. Issue 1 (March 2016) - Ubacht, Jolien
The transition from a former monopolistic towards a more competitive market in newly liberalized network-based markets raises regulatory issues. National Regulatory Authorities (NRA) face the challenge to deal with these issues in order to guide the transition process. Although this transition process is widely studied, an integral view on the regulatory process itself remained absent. This raises the research question how NRAs deal with the regulatory issues while aiming for competition engineering. By following a Grounded Theory approach we analyzed the regulatory practice of three NRAs in newly liberalized mobile telecommunications markets during a five-year period. Our study reveals a high variety in procedural activities that represent the complexity of the regulatory process. Insight into these activities is informative for regulatory processes that need to determine the appropriate governance arrangements in complex, dynamic markets in which the institutions and technology go through a continuous co-evolutionary process. Firmly based in empirical data we present the theoretical concept of mixing and matching which represents the way in which activities are mixed during the regulatory process and matched with the issue that requires a governance arrangement. Further research into regulatory practice in other newly liberalized network-based markets will lead to a formal theory of regulatory practice as a process. This study contributes to the domain of regulatory studies by focusing on the procedural aspects of regulatory practice in newly liberalized network-based markets.